(untitled) (Development Service Industry Management, 2023)
The article examines the essence of the concept of "development". Development is a very controversial and difficult to measure process, which is not implemented in a straight line, but in a spiral. It is characterized by unevenness, which includes periods of growth and decline, leads to quantitative and qualitative changes in the company’s activities, creates positive and negative phenomena and trends. From the point of view of economic analysis, development is divided into two groups of factors, in particular, extensive and intensive. In the scientific literature, there are different approaches to managing the development of an enterprise. The strategic approach to managing the development of the enterprise is most often used and aims to develop certain actions to overcome the identified problem in the process of implementing the enterprise strategy. A comprehensive approach involves the application of all aspects of development (technical, environmental, economic, organizational, etc.). The system approach involves considering the development (object) as a set of interconnected elements. The evolutionary approach consists in recognizing the factors of the changing external environment, which is the main driving force for the development and change of the business entity. The adaptive approach involves the search for effective options for making managerial decisions aimed at creating a mechanism for adapting the development of enterprises in a competitive environment. The process approach allows you to focus on the results of the enterprise’s work, it changes the concept of the organization’s structure, since the main element becomes the process. The innovative approach is based on the activation of the innovative activity of the enterprise. The integration approach involves organizational and economic transformation. The marketing approach is a consumer-oriented activity and management decision-making from the point of view of market requirements. The regulatory approach consists in establishing management standards for all management subsystems and their compliance. The resource approach assumes the existence of a connection between the company’s resources and its success in a competitive environment. The synergistic approach involves the application of the laws of self-organization of systems. The situational approach is based on the fact that there is not and cannot be a universal method of managing an organization that would be suitable universally, therefore, the management of an organization must be carried out depending on the situation. The functional approach involves considering the object as a holistic process of implementing management functions. A targeted approach to managing the development of an enterprise involves an orientation towards achieving the set goal.